Experiência comunicativa na prática do crossfit: processos intersubjetivos e estéticos - LIMA, Rebeca dos Santos (Universidade Federal do Pará, 2018)
This research is part of the researcher's insertion in a CrossFit box, observing and experiencing the moments during, during and after training, in the search for understandings that understand the communicative experiences produced among the practitioners of the sport. These symbolic interactions of the current life of a contemporary urban micro-society will be described through an ethnographic account. From the perception of intersubjective dimensions of belonging and production of affective meanings, we will discuss the field data from a theoretical reference that includes the notions of Aesthetics (Maffesoli), Intersubjectivity (Schutz), Typification (Schutz) and Conflict (Simmel), related to the uses of the Body (Mauss) and its Performances (Schechner). This theoretical reference seems to us propitious to interpret the communicative phenomena perceived during field research, since the study of intersubjectivity corresponds to a new perspective of analysis of communicative phenomena. This approach comprises communication as the structuring phenomenon of cultural mediations of social life. So here we intend to approach communication as knowledge that falls within the sphere of the action of human experience, behind that which is relational and shared.